Intercultural Communications and Conductive Hearing Loss - Howard, Damien (First Peoples Child & Family Review, 2007)
Widespread conductive hearing loss among Aboriginal peoples in ﬁrst world nations has a signiﬁcant, although largely invisible impact on intercultural communication. Poor acoustics and cultural differences in communication styles compound the effect of widespread hearing loss among Aboriginal peoples. This article considers Australian research that has investigated how conductive hearing loss can impact on intercultural communication in schools and in the criminal justice system, as well as communication processes within Aboriginal families. An understanding of these issues can facilitate the development of innovative interventions that can help address Aboriginal disadvantage, especially within mainstream institutions.